The Effects of Participatory Forest Management Projects on the Livelihoods of Communities Adjacent to Forests - Kyalo, Justin (International Journal of Social Sciences and Information Technology, 2016)
This study examines the effects of participatory forest management projects on the livelihoods of communities adjacent to forests. Previously, such projects were government led through a top-down approach and this prevented the communities from participating equally despite the fact that they were equal partners. The study therefore gives a comparison between the effects of the participatory forest management projects and the non-participatory ones used before. The central concept of the new paradigm is to grant exclusive user rights to organized user groups among the forest communities. The approach empowers the forest dependent communities to become organized and obtain access to the forest resource coupled with clearly defined rights and responsibilities. As a result the user groups are now living in harmony with their forests, their incomes have increased, adoption of alternative means of livelihoods, food security has improved, interactions among themselves and with authorities has also been enhanced and generally there has been an improvement in the use of forestry products. Additionally, experience gained from this approach has contributed to the consideration of community forestry as a viable pathway for forest conservation in the country. The study mainly relied on secondary data which comprised of journal articles. Scaling up such an innovative approach would serve to improve livelihoods of communities adjacent to forests while at the same time enhancing sustainable management of forests
Keywords: Participatory forest management; Livelihoods; Forest communities; User groups